NATIONAL INTEREST AS A BASIS OF THE GOVERNMENT COOPERATION WITH PRIVATE COMPANIES IN PROVIDING THE PALAPA RING INFRASTRUCTURE - Khoirunnisa; Faizal Kurniawan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this study to analyze the criteria of national interest that become the basis of the cooperation agreement between the Indonesian Government and private companies as well as the characteristics of the deal in providing the Palapa Ring infrastructure. This study is normative research that applies the statute approach and conceptual approach. The legal materials used comprise both primary and secondary materials. The results show that the national interest in Public-Private Partnership (PPP) has several criteria. First, the production branch, which involves people's lives is undoubtedly the object of the cooperation between the Government and private companies. Second, there are mandatory rules that are closely related to the public order in the infrastructure provision with private companies. The Indonesian Government attempts to meet the public needs in the telecommunication sector by establishing the Palapa Ring project to prosper the Indonesian people with technological capabilities. The infrastructure provision is made by building partnerships with private companies within an agreement. National interest in PublicPrivate Partnership (PPP) is merely to avoid losses that Indonesia may go through. Thus, the economic and social welfare regulations in Article 33 of the 1945 Constitution of the Republic of Indonesia are to be further studied. Moreover, private companies are interested in building cooperation with the Indonesian Government in providing telecommunication infrastructure in Indonesia.